THE EFFECT OF COOKING TIME ON THE NUTRITIONAL CONTENT OF THE MUDSKIPPERFISH FLOUR (Periopthalmodon schlosseri) - Nita Grecia Damanik; Mirna Ilza; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTMudskipper(Periopthalmodon schlosseri)had a local nameknownas tembakulfish that could be found in mangroves or mangrove forests. Tembakulfish hadhigh nutritional content because of its high protein contentup to81.22%intembakul fish meat. The research aimed to determine the effect of cooking time on the nutritional valuein the fish flour (proximateand mineral content) and to determine the optimum cooking time. Theresearch used a non-factorial Completely Randomized Design (CRD) consisting 3 different treatment time (60, 75 and 90 minutes)at a temperature of 1000C. The results showed that the different cooking time were not significantly affecting to the physical appearance of the fish flourproduced, those were brownish yellow colour. The treatment of cocking fish for 60 minutesproduced the best fish flour, indicated by the highest yield up to 21.55%, that wascontainingwater 12.67% (bk),ash4.69% (bk), protein 80.74% (bk), fat 1.48% (bk) and several minerals includingpotassium 0.71% (bk), calcium 15.15% (bk),iron 0.05% (bk), zinc 0.04% (bk), and phosphorus 0.13% (bk). Keywords: fishflour, nutritional content, tembakul fish,